2016
DOI: 10.1002/chem.201604602
|View full text |Cite
|
Sign up to set email alerts
|

N‐Methylanilines as Simple and Efficient Promoters for Radical‐Type Cross‐Coupling Reactions of Aryl Iodides

Abstract: Activation of the carbon-halogen bonds in aryl halides is a key step in transition-metal-free cross-coupling reactions. In this paper, a new and efficient radical initiation system for the activation of iodoarenes to produce aryl radicals was discovered, which employs the combination of N-methylanilines and tBuOK. This radical initiation system is robust and versatile, enabling various types of aryl-radical-related reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 115 publications
(152 reference statements)
0
19
0
Order By: Relevance
“…3,5‐Dimethyl‐1,1′‐biphenyl: Table , Entry 6. Prepared from 1‐iodo‐3,5‐dimethylbenzene and phenylmagnesium bromide according to the general procedure.…”
Section: Methodsmentioning
confidence: 99%
“…3,5‐Dimethyl‐1,1′‐biphenyl: Table , Entry 6. Prepared from 1‐iodo‐3,5‐dimethylbenzene and phenylmagnesium bromide according to the general procedure.…”
Section: Methodsmentioning
confidence: 99%
“…To verify this process, 2a was subjected to the standard reaction conditions with deuterated N -methylaniline 1a - D , and the desired isotope-substituted product 3aa - D was isolated (Scheme ). This showed that the proton for hydroamination came from secondary amines (see the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that, N -methylaniline serves as an efficient promoter for the activation of iodoarenes in the presence of t -BuOK, where N -methylanilide anion acts as an electron donor. 7 However, attempts to enable the activation of bromoarene 1a by structural tuning of the N -methylaniline promoter proved unsuccessful ( Scheme 2a ). Although electron-rich anilines exhibited slightly better activities ( 2a–e ), the results were far from satisfactory, and the attachment of an additional aromatic ring to aniline (either as a substituent or as a fused cycle, 2f–h ) with the aim to assist SET by stabilizing the formed N-centered radical, was also useless.…”
Section: Resultsmentioning
confidence: 99%
“… 1 In addition to stoichiometric metalation 2 or transition-metal catalysis 3 for C–X bond activation, in recent years the development of small-organic-molecule-promoted C–X bond activation has attracted great attention. A series of small organic molecules, such as 1,10-phenanthrolines, 4 1,2-diamines, 5 1,2-diols 6 and N -methylanilines, 7 were found to promote the activation of haloarene in the presence of a base, producing a reactive aryl radical intermediate which undergoes substitution processes (referred to as base-promoted homolytic aromatic substitution, BHAS). 8 Careful mechanistic studies revealed that the promoter is transformed into a “super electron donor” under the reaction conditions, which then initiates the cleavage of the C–X bond by single electron transfer (SET) to the haloarene substrate ( Scheme 1a ).…”
Section: Introductionmentioning
confidence: 99%